Efecto de los tratamientos silvopastorales en el crecimiento del alcornoque (Scientia gerundensis, 1999)
Comparative effects of shrub clearing and grazing on the apical and radial growth of the cork oak have been studied in four cork oak wood stations. Shoot growth segments and annual wood rings were measured in 10 selected trees in every plot. Average shoot elongation's oscillate between 2.5 to 4.8 cm; annual wood rings from 0.95 to 2.05 mm and annual radial growth of wood plus cork from 2.3 to 5.7 mm. Significative differences were found between silvo-pastoral treatments in relation to apical elongation. In treated plots, the apical growth of segments that reach the maximum elongation can be a 75% higher than in control plots. This increment on shoot growth can be explained by the decrease in plant competition and by the nutrient contribution of grazing. No significative effects of treatments on radial growth have been found.